Propostas para a gestão de resíduos no hospital veterinário universitário da UFSM - Silva Filho, Daves Pereira da (2011)
Human hospitals, veterinary hospitals, clinics and dentistry offices generate waste that might pose risks to health and environment, in certain circumstances. In Brazil, ANVISA s RDC standard and CONAMA s Resolution nº 358/05, establish rules for preparation of a waste management plan for health services in general. This research was done based on standards and literature review, and it is a case study at the Veterinary Hospital of Federal University of Santa Maria. Based on data collected and current law, the work has, as one of the objectives, review the hospital s management plan and propose changes, if necessary. We observed that Class A (infectious) and Class D (domestic) waste are generated in larger quantities, and among non-conformities found, the biggest problems were in segregation and packaging of these waste classes. Given these results and observations during the study, changes were proposed, both in PGRSS as waste gathering mode and, specifically, training and supervision.